Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1038/s41560-022-01039-0
|View full text |Cite
|
Sign up to set email alerts
|

Modulating crystal growth of formamidinium–caesium perovskites for over 200 cm2 photovoltaic sub-modules

Abstract: Upscalable fabrication of efficient and stable perovskite solar modules is urgently needed for commercialization. Herein, we introduce methylammonium chloride (MACl) additives in the cosolvent system of N-methyl-2-pyrrolidone (NMP) / N,N-dimethylformamide (DMF) to control the formation of intermediate phases during the growth of formamidinium (FA)-cesium (Cs) lead triiodide perovskite films. We achieve high quality films upon drying without the use of antisolvent.By implementing bulk and surface passivation, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
94
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(108 citation statements)
references
References 49 publications
0
94
0
Order By: Relevance
“…The main solvent favors nucleation and growth by quickly evaporating, while the cosolvent can stabilize the precursor ink (widen the processing window) by strong interaction with the Pb 2+ center. Very recently, Qi and coauthors [109] revealed that N-methyl-2-pyrrolidone can impede the formation of the perovskite-DMF complex intermediates that lead to poor film quality. Combining the introduction of MACl, they achieved an efficiency of 15.3% on a module area of 205 cm 2 .…”
Section: Blade Coatingmentioning
confidence: 99%
“…The main solvent favors nucleation and growth by quickly evaporating, while the cosolvent can stabilize the precursor ink (widen the processing window) by strong interaction with the Pb 2+ center. Very recently, Qi and coauthors [109] revealed that N-methyl-2-pyrrolidone can impede the formation of the perovskite-DMF complex intermediates that lead to poor film quality. Combining the introduction of MACl, they achieved an efficiency of 15.3% on a module area of 205 cm 2 .…”
Section: Blade Coatingmentioning
confidence: 99%
“…To address these issues, various strategies have been attempted, such as additive engineering [ 23 , 24 , 25 , 26 , 27 , 28 ], interfacial modification [ 29 , 30 , 31 , 32 , 33 , 34 ], solvent engineering [ 2 , 35 ] and so on. Among them, the incorporation of one-dimensional (1D) perovskite has drawn great attention due to its unique characteristics in terms of stability [ 36 , 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…21 Overall, to obtain efficient, stable scaled-up PSCs, the exploitation of coordination-induced crystallization regulation, and the formation of desirable intermediate phases during the growth of an MA or FA-Cs-based perovskite film can therefore lead to high-performance PSCs. 22 Contributions detailing the transfer of this understanding to large-scale printing are scarce. We start with the description of printing methods currently reported for perovskite PSCs and summarize perovskite phase transition during fabrication.…”
mentioning
confidence: 99%
“…Qi and co-workers developed a lead halide-templated crystallization process for printing large-area FA-based perovskite films and minimized the formation of DMF complex intermediates that could induce dendritic crystals . Overall, to obtain efficient, stable scaled-up PSCs, the exploitation of coordination-induced crystallization regulation, and the formation of desirable intermediate phases during the growth of an MA or FA-Cs-based perovskite film can therefore lead to high-performance PSCs …”
mentioning
confidence: 99%